the Numidian-Greek relations during (203-46 BC) - saidi, salim (The Algerian Historical Journal, 2026)
The aim of this study is to examine on the origins of the Numidian-Greek relations in fields political, trade civilizations relations, When the Numidian king reached the throne in 203 BC, he started a new era for his kingdom. The Numidian state opened up to the peoples of the Mediterranean and entered into relations with neighboring countries. The Greek cities were among the most significant areas that had political and economic relations with Numidia. This evident throughout the discovery of many material remains in the Numidian kingdom, such as jars, pottery lamps and metal utensils, as well Greek communities lived in the capital, Cirta, The results that reached which resulted in an important cultural harmony that was evident in the adoption of this Punic deities, and this is confirmed by several inscriptions found in the Alhofra temple. In return, the Greeks build monuments and statues to Massinissa, Gulussa, and Hiempsal II as a thank and an acknowledgment of their gratituded. But the cultural influences, especially the linguistic ones, remained limit to the royale palace and the Numidian elite.